High pressure structural investigations on hexagonal YInO3. Issue 1 (2nd January 2019) - Dwivedi, Abhilash; Poswal, H. K.; Shukla, R.; Velaga, Srihari; Sahoo, B. D.; Grover, V.; Deo, M. N.
ABSTRACT: Hexagonal (space group P63 cm ) form of YInO3 has been investigated under high pressure using synchrotron-based angle-dispersive X-ray diffraction and Raman scattering methods. Our experimental investigations suggest that it undergoes the phase transition to a new phase in the pressure range 12–15 GPa, while the ambient hexagonal phase is found to coexist with the new phase up to 29 GPa. DFT based calculations within the LDA approach on the hexagonal phase of YInO3 showed that the unit cell volume matches well with the experimentally obtained volume at ambient pressure. As the pressure increases, theoretically obtained values of unit cell volume of the hexagonal phase were found to be significantly lower than that of experimentally obtained values. This discrepancy has been corrected using LDA + UIn(4d) (Hubbard interaction parameter between Indium 4 d electrons) method. We have proposed the high pressure phase of YInO3 to be orthorhombic with space group Pnma .